2018
DOI: 10.1080/14786419.2018.1512990
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and cytotoxic activities of phenolic constituents from the stem extracts of Spatholobus parviflorus

Abstract: A new 2-arylbenzofuran, spathobenzofuran (1), together with ten known compounds including a 2-arylbenzofuran, three pterocarpans and six isoflavones were isolated from the acetone crude extract of the stems of Spatholobus parviflorus. All compounds were characterised by spectroscopic methods. Compound 4 was active (MIC 8 µg/mL) against Gram-negative Pseudomonas aeruginosa TISTR 781 while compound 2 had modest activity against Gram-positive Staphylococcus aureus TISTR 1466 with a MIC value of 16 µg/ mL. All iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…has been known as a botanical source of these specific propolis ( Table 1 ). Two compounds, medicarpin and vestitol, that were frequently isolated in these HBP, both exhibited antibacterial activity [ 171 , 172 ]. Moreover, medicarpin was found as a potential anticancer and bone healing agent [ 173 , 174 ], while vestitol showed potent antioxidant and anti-inflammatory properties [ 171 , 175 , 176 ] ( Table 2 ).…”
Section: Propolis Components: Chemistry and Geographical Distributmentioning
confidence: 99%
“…has been known as a botanical source of these specific propolis ( Table 1 ). Two compounds, medicarpin and vestitol, that were frequently isolated in these HBP, both exhibited antibacterial activity [ 171 , 172 ]. Moreover, medicarpin was found as a potential anticancer and bone healing agent [ 173 , 174 ], while vestitol showed potent antioxidant and anti-inflammatory properties [ 171 , 175 , 176 ] ( Table 2 ).…”
Section: Propolis Components: Chemistry and Geographical Distributmentioning
confidence: 99%
“…Kuntze respectively, which were related biogenetically to the flavonoids. 5,48 Specially, rotenone (80), a kind of isoflavonoids, whose carbon skeleton number is different from that of traditional flavonoids, has been reported from S. parviflorus (DC.) Kuntze.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Evidences suggested that vignafuran and (6aR,11aR)-medicarpin presented good activities against Staphylococcus aureus and Pseudomonas aeruginosa with a minimum inhibitory concentration (MIC) value of 16 μg mL −1 and 8 μg mL −1 , respectively. 5 It should be noted the above studies only used in vitro methods, which failed to fully understand the information on the effect and action mechanisms. Fortunately, these findings may prompt further extensive investigations into the in vivo antimicrobial activities as well as the structure–activity relationship, which would benefit in screening effective antimicrobial drugs with low toxicity.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, medicarpin can lead to apoptosis and reverse multidrug resistance in P388 leukemia cells (IC 50 ≈ 90 μM) [30]. It also has antifungal [31] and antibacterial activities [32]. Additionally, medicarpin can stimulate mesenchymal stem cells to differentiate into brown and beige adipocytes via the adenosine monophosphate-activated protein kinase (AMPK) pathway and boost lipolysis in adipocytes via a protein kinase A (PKA)-dependent pathway, so it is expected to be a potential drug for the treatment of obesity [33,34].…”
Section: Introductionmentioning
confidence: 99%